Blasting the continuum of history: Walter Benjamin’s "now-time" and the recovery of experience - Torbidoni, Juan Manuel (THÉMATA. Revista de Filosofía, 2021)
This paper analyses the concept of “now-time” (Jetztzeit) in Walter Benjamin’s “On the concept of history.” It shows its centrality in Benjamin’s philosophy of history, by defining it in opposition to two elements of Kantian philosophy: on the one hand, “empty, homogeneous time,” on the other, the faith in the infinite, inevitable progress of a generic “mankind.” It argues that the notions of now-time and truth as flitting hark back to Benjamin’s early concern about the devaluation of experience in modern philosophy and the need to rescue the ephemeral as a decisive element in metaphysics. Rather than a historical category, now-time denotes an instance of redemption.